Jumlah Piutang BLUD Air Minum Kota Cimahi Sebelum dan Sesudah Penerapan SOP Penertiban Pelanggan - Bahiyyah, Khariidatul; Yuyun Kurniawati; Harnavela Sofyan; Mulki Asyriyanti (EKOBIMA, 2024)
Standard Operating Procedure (SOP) is a work guideline so that activities within the company can be controlled so that targets are achieved optimally. Based on the results of observations during research at BLUD Air Minum Cimahi. The implementation of the customer control SOP went quite smoothly, while the obstacle faced was the error in providing an Arrears Notification Letter which had not been updated and was not due. There are 5 parts involved and 27 procedures that must be followed. The research method used is descriptive qualitative with an observational approach. The results of this research show that the amount of receivables after implementing the customer control SOP decreased by IDR 69,278,500.